2007
DOI: 10.1016/j.idairyj.2006.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Flow behaviour of inulin–milk beverages. Influence of inulin average chain length and of milk fat content

Abstract: The effects of the addition of different types of inulin (oligofructose, native and long chain) at different concentrations (2%, 4%, 6%, 8% and 10%, w/w) on the flow behaviour of milk beverages model systems were studied. The flow of the inulin-milk solutions was Newtonian, except for whole milk samples with higher long chain inulin concentrations (8% and 10%), which were shear thinning. All inulin-k-carrageenan-milk samples were shear thinning. The viscosity of 3.1% fat whole milk could be approximated by ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 27 publications
5
59
0
1
Order By: Relevance
“…Worldwide, growing awareness of the physiological benefits of dietary fiber, among consumers, coupled with the ready availability of commercial dietary fiber preparations, led to the successful development of various dietary fiber fortified dairy products such as yoghurt (Fernandez-Garcia and McGregor 1997;Fernandez-Gracia et al 1998;Staffolo et al 2004;Garcia-Perez et al 2005;Aportela-Palacios et al 2005; Kip et al 2006;Guggisberg et al 2009), cheese (Buriti et al 2007Cardarelli et al 2008), imitation cheese (Hennelly et al 2006), ice cream (Singh et al 2005;, probiotic ice-cream (Akalin and Erisir 2008), yog-ice cream (El-Nagar et al 2002;Ahmadi et al 2012), dairy dessert (Tarrega and Costell 2006), lactic beverage (de-Castro et al 2009;Villegas and Costell 2007). In India, some traditional milk-based confections like gajar-pak (milk-carrot based), giya-ka-halwa (milk-bottle gourd based), doda-burfi (milkwheat based), kaju-burfi (milk-cashew nut based); cerealsbased milk desserts like kheer and dalia (Patel and Arora 2005) and milk-cereal based beverages like raabadi (Pal 2008;Modha and Pal 2011) contain significant quantities of dietary fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, growing awareness of the physiological benefits of dietary fiber, among consumers, coupled with the ready availability of commercial dietary fiber preparations, led to the successful development of various dietary fiber fortified dairy products such as yoghurt (Fernandez-Garcia and McGregor 1997;Fernandez-Gracia et al 1998;Staffolo et al 2004;Garcia-Perez et al 2005;Aportela-Palacios et al 2005; Kip et al 2006;Guggisberg et al 2009), cheese (Buriti et al 2007Cardarelli et al 2008), imitation cheese (Hennelly et al 2006), ice cream (Singh et al 2005;, probiotic ice-cream (Akalin and Erisir 2008), yog-ice cream (El-Nagar et al 2002;Ahmadi et al 2012), dairy dessert (Tarrega and Costell 2006), lactic beverage (de-Castro et al 2009;Villegas and Costell 2007). In India, some traditional milk-based confections like gajar-pak (milk-carrot based), giya-ka-halwa (milk-bottle gourd based), doda-burfi (milkwheat based), kaju-burfi (milk-cashew nut based); cerealsbased milk desserts like kheer and dalia (Patel and Arora 2005) and milk-cereal based beverages like raabadi (Pal 2008;Modha and Pal 2011) contain significant quantities of dietary fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Inulin is a natural non-digestible storage polysaccharide Acta Alimentaria 46, 2017 consisting of GF n (fructans starting with glucose) and F m (fructans starting with fructose) compounds, in which m and n are the numbers of fructose units that are interconnected with β (2-1) bounds ending in a terminal glucose (G) molecule (ALIMI et al, 2013). Long-chain inulin is also increasingly used as a prebiotic gelling/thickening agent in food products specially dairies (VILLEGAS & COSTELL, 2007). These properties are attributed to the formation of small aggregates composed of physically interacted inulin micro-crystals that can bind a signifi cant amount of water and thereby create an appropriate mouth feeling, smooth and creamy texture (BOT et al, 2004).…”
mentioning
confidence: 99%
“…Several studies are available in the literature with regards to the effect of inulin addition on physical and sensory properties of dairy products. Villegas and Costell (2007) reported that the addition of inulin (@4-6%) to skimmed milk beverages was found to increase the viscosity, approximating it to that of 3.1% fat beverages. Similar effect was also observed upon addition of 6% inulin to low-fat custard with low starch concentration (2.5 and 3.25%) (Tarrega and Costell, 2006).…”
Section: Replacement Of Fat or For Some Technological Benefitsmentioning
confidence: 99%